ANALYSIS OF CUSTOMER PERCEPTION ON PAYMENT BANKING SERVICES IN SIVAGANGA DISTRICT - Mr. V. Dinesh* and Dr. R. Venkatesan** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
People's lifestyles have changed dramatically, the worth of technology-driven banking system is growing by day-to-day. Consumers are too busy to visit banks to deposit or withdraw money. The Reserve Bank of India's most recent project, payments banks, was introduced with the intention of offering digital, cashless, and paperless banking options in India. It is a unique and distinctive bank service designed to cater specifically to the beneath banked and unbanked citizens of the nation. Payments banks aim to cater to clients who require ongoing financial services at a minimal cost of service. Moreover, it benefits low-income individuals and migrant workers. They are linked to the formal banking system and the economy through payment banks. It also offers the benefit of safe, technology-driven transactions, which could make money exchanges easier. This paper analyses the customer perception towards the payment services of bank in Sivaganga district and analysed by the factor analysis method. Each factors were segregated into four constructs such as “Perception about Service Quality of Payments Bank, Perception about Easy money transfer of Payments bank, Perception about prospects of Payments bank, Perception about Marketing Strategies”. The study is to determining the level of customer perception of Payments Bank services. As a result, the practicability of payments bank services to customers is examined in the current context. The study analysed the secure of money transaction, technology-driven, cutting-edge of financial service to the small enterprises and making the right choices to raise the caliber of services offered by payment banks.